Service quality and inpatient satisfaction at Kendari City General Hospital - Muhammad Al Rajab; Fajar Kurniawan (Poltekkes Kemenkes Bandung, 2026)
Background: Service quality is an important indicator in evaluating hospital performance and determining patient satisfaction. The increasing number of inpatient admissions at Kendari City Regional General Hospital (RSUD Kota Kendari) is not always accompanied by an increase in facility capacity and healthcare personnel, which may affect service quality and patient satisfaction. Therefore, an evaluation of service quality based on the SERVQUAL model is necessary to identify the factors that most strongly influence inpatient satisfaction. Objective: This study aimed to analyze the influence of SERVQUAL dimensions, tangibles, reliability, responsiveness, assurance, and empathy on service quality and their impact on inpatient satisfaction at RSUD Kota Kendari. Methods: This study employed a quantitative design with a cross-sectional approach conducted from May to June 2025 at RSUD Kota Kendari. A total of 233 inpatients were selected from a population of 554 patients using a purposive sampling technique. Data were collected using a SERVQUAL-based questionnaire that had been tested for validity and reliability. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. Results: All SERVQUAL dimensions had a positive and significant effect on service quality and patient satisfaction. The empathy dimension showed the most dominant influence (f² = 1.940), while service quality had a significant effect on patient satisfaction with a path coefficient of 0.677. Conclusion: Improving hospital service quality should emphasize the empathy of healthcare professionals, as positive interpersonal interactions are a key factor in enhancing inpatient satisfaction.